Noncanonical microRNAs and endogenous siRNAs in normal and psoriatic human skin - Xia, Jing (Oxford University Press, 2013)
Noncanonical microRNAs (miRNAs) and endogenous small interfering RNAs (endo-siRNAs) are key gene regulators in eukaryotes. Noncanonical miRNAs, which bypass part of the canonical miRNA biogenesis pathway, can originate from a variety of genomic loci, which include small nucleolar RNAs (snoRNAs), transfer RNAs (tRNAs) and introns, whereas endo-siRNAs can arise from repetitive elements, some of which are transposable. The roles of noncanonical miRNAs and endo-siRNAs in complex diseases have yet to be characterized. To investigate their potential expression and function in psoriasis, we carried out a comprehensive, genome-wide search for noncanonical miRNAs and endo-siRNAs in small RNA deep-sequencing data sets from normal and psoriatic human skin. By analyzing more than 670 million qualified reads from 67 small RNA libraries, we identified 21 novel, noncanonical miRNAs (3 snoRNA-derived and 2 tRNA-derived miRNAs and 16 miRtrons) and 39 novel endo-siRNAs that were expressed in skin. The expression of four novel small RNAs was validated by qRT–PCR in human skin, and their Argonaute association was confirmed by co-immunoprecipitation of ectopic small RNAs in HEK293 cells. Fifteen noncanonical miRNAs or endo-siRNAs were significantly differentially expressed in psoriatic-involved versus normal skin, including an Alu-short interspersed element-derived siRNA which was 17-fold up-regulated in psoriatic-involved skin. These and other differentially expressed small noncoding RNAs may function as regulators of gene expression in skin and potentially play a role in psoriasis pathogenesis.